Effect of Zingiber Officinale (Ginger Rhizomes) Hydroethanolic Extract on Hyoscine-Induced Memory Impairment in Adult Male Rats - Ali Gomar (International Clinical Neuroscience Journal, 2015)
Background: The spice Zingiber officinale or ginger possesses antioxidant activity and neuroprotective effects. In this study we hypothesized that treatment with hydroethanolic extract of ginger (50, 100 and 200 mg/kg, p.o) would effect on the hyoscine-induced memory impairment in rats. Methods: In this experimental study 64 male Wistar rats were divided into eight groups (8 rats in each group): normal saline, hyoscine (1 mg/kg), ginger extract (50, 100 and 200 mg/kg), or hyoscine (1 mg/kg) plus ginger extract (50, 100 and 200 mg/kg). Memory impairment was induced by a single injection of hyoscine (1 mg/kg, i.p). Cognitive functions were evaluated using passive avoidance learning (PAL) task. Retention test was carried out 24 h after training, and the latency of entering the dark compartment [step-through latency (STL)] and the total time in the dark compartment (TDC) were recorded. All statistical analysis was carried out at 5% level of significance using SPSS version 21. The data were analyzed by ANOVA followed by Tukey’s test. Results: The time latency in hyoscine-treated group was lower than control (133.87±14.60 vs. 242.12±10.58; p<0.001, respectively). Treatment of the animals by 100 and 200 mg/kg of ginger extract before the training trial increased the time latency at 24 h after the training trial (277±4.67 and 280.37±7.68; p<0.01, respectively). Administration of both 100 and 200 mg/kg doses of the extract in hyoscine received animal groups before retention trials also increased the time latency than the hyoscine-treated groups (247.37±7.62 and 271.87±9.11; p<0.001, respectively). Conclusion: The results revealed that the ginger hydroethanolic extract attenuated hyoscineinduced memory impairment.